SYSTEMATIC LITERATURE REVIEW: PENERAPAN MODEL CONTEXTUAL TEACHING AND LEARNING DALAM MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA - Lina Fitriyani; Heni Pujiastuti (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
This study systematically examines the application of the Contextual Teaching and Learning (CTL) model in improving students’ mathematical problem-solving skills. Through a Systematic Literature Review of articles indexed in SINTA 1–6 from 2021 to 2026, a total of 25 studies were identified that discussed the effectiveness of CTL in mathematics education across various educational levels. The search was conducted in a national database using a combination of keywords: Contextual Teaching and Learning, CTL, Mathematical Problem Solving, and students’ mathematical abilities, followed by selection through the identification, screening, eligibility, and inclusion stages based on the PRISMA framework. A synthesis of the findings indicates that the consistent application of CTL has a positive impact on improving students’ mathematical problem-solving skills, particularly in understanding problems, designing strategies, and executing solutions. Contextual learning also encourages active student engagement and helps them connect mathematical concepts to real-life situations, thereby making the learning process more meaningful. However, variations in student performance are still observed, particularly during the evaluation and conclusion-drawing stages, which are influenced by cognitive and affective factors as well as the quality of instructional implementation. Various instructional innovations, such as the integration of digital media and the development of CTL-based instructional materials, have been reported to enhance the effectiveness of this approach. This study underscores the importance of implementing planned and adaptive contextual learning as a means to improve students’ mathematical problem-solving skills. ABSTRAK Penelitian ini mengkaji secara sistematis penerapan model Contextual Teaching and Learning (CTL) dalam meningkatkan kemampuan pemecahan masalah matematis siswa. Melalui pendekatan Systematic Literature Review terhadap artikel terindeks SINTA 1–6 pada rentang tahun 2021–2026, teridentifikasi sebanyak 25 studi yang membahas efektivitas CTL dalam pembelajaran matematika pada berbagai jenjang pendidikan. Pencarian dilakukan pada basis data nasional menggunakan kombinasi kata kunci Contextual Teaching and Learning, CTL, Mathematical Problem Solving, serta kemampuan pemecahan masalah matematis, kemudian diseleksi melalui tahap identifikasi, penyaringan, kelayakan, dan inklusi berdasarkan kerangka PRISMA. Sintesis temuan menunjukkan bahwa penerapan CTL secara konsisten memberikan dampak positif terhadap peningkatan kemampuan pemecahan masalah matematis siswa, terutama dalam memahami masalah, merancang strategi, dan melaksanakan penyelesaian. Pembelajaran kontekstual juga mendorong keterlibatan aktif siswa serta membantu mereka mengaitkan konsep matematika dengan situasi kehidupan nyata sehingga proses belajar menjadi lebih bermakna. Namun demikian, masih ditemukan variasi kemampuan siswa, khususnya pada tahap evaluasi dan penarikan kesimpulan, yang dipengaruhi oleh faktor kognitif dan afektif serta kualitas implementasi pembelajaran. Berbagai inovasi pembelajaran, seperti integrasi media digital dan pengembangan bahan ajar berbasis CTL, dilaporkan mampu memperkuat efektivitas pendekatan ini. Kajian ini menegaskan pentingnya penerapan pembelajaran kontekstual yang terencana dan adaptif sebagai upaya meningkatkan kemampuan pemecahan masalah matematis siswa.